Human Knowledge : Its Scope and Limits - Russell, Bertrand, 1872-1970 (London ; New York Routledge, 2012)
How do we know what we 'know'? How did we - as individuals and as a society - come to accept certain knowledge as fact? This title questions the reliability of our assumptions on knowledge. It investigates the relationship between 'individual' and 'scientific' knowledge
Include Index
Keywords: Knowledge, Theory of